HUBUNGAN ANTARA DURASI DUDUK DENGAN TIGHTNESS OTOT HAMSTRING PADA PEDAGANG DI PANTAI KUTA, KABUPATEN BADUNG - Ni Putu Intan Sekarini; I Putu Yudi Pramana Putra; Ari Wibawa; Made Hendra Nugraha (KOLONI, 2026)
Prolonged sitting duration is part of sedentary behavior that can affect muscle condition, particularly the hamstring muscles. Sitting for extended periods causes the hamstring muscles to remain in a continuously shortened position, which may lead to hamstring muscle tightness. Traditional market sellers are one of the occupational groups at risk of experiencing this condition due to their work activities, which are dominated by long sitting duration. Therefore, this study aimed to determine the relationship between sitting duration and hamstring muscle tightness among traditional market sellers at Kuta Beach.This study used an observational analytic design with a cross-sectional approach. The subject consisted of 52 selected using purposive sampling technique. Sitting duration data were obtained through interviews using a questionnaire, while hamstring muscle tightness was measured using the Active knee extension method. Data were analyzed using the Spearman rho test to determine the relationship between sitting duration and hamstring muscle tightness.The results showed that most traditional market sellers had long sitting duration and experienced moderate to severe hamstring muscle tightness. Statistical analysis showed a significant relationship between sitting duration and hamstring muscle tightness (p = 0.002) with a moderate correlation strength (r = 0.420) and a positive direction, indicating that longer sitting duration is associated with higher levels of hamstring muscle tightness.In conclusion, sitting duration has a significant relationship with hamstring muscle tightness among traditional market sellers at Kuta Beach. Therefore, reducing prolonged sitting duration and performing regular stretching are recommended to prevent increased hamstring muscle tightness among traditional market seller.